2015
DOI: 10.1039/c5ta02524a
|View full text |Cite
|
Sign up to set email alerts
|

High electrochemical performance and lithiation–delithiation phase evolution in CuO thin films for Li-ion storage

Abstract: Magnetron sputtered CuO thin films with hierarchical structure and large specific surface were prepared, and their electrochemical properties and reaction characteristics as the Li-ion storage electrodes were investigated. The nanostructured CuO thin film showed a high capacity, good cycling stability and excellent rate performance, exhibited the discharge capacities of 703 mAh/g at 100 mA/g and 465 mAh/g at 1000 mA/g even after 100 electrochemical cycles. Transmission electron microscopy was applied to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 51 publications
3
15
0
Order By: Relevance
“…However, at the end of first cycle (delithiation), Cu 4 O 3 was observed to be major phase while Cu 2 O and CuO were minor phase. Cu 4 O 3 has been observed before in thin‐film electrodes by TEM and here we observed Cu 4 O 3 phase in composite electrodes. At the end of delithiation, most of the composite electrodes show reversible Cu 2 O phase rather than Cu 4 O 3 ,, which explains the high capacity reported in the present work.…”
Section: Introductionsupporting
confidence: 85%
“…However, at the end of first cycle (delithiation), Cu 4 O 3 was observed to be major phase while Cu 2 O and CuO were minor phase. Cu 4 O 3 has been observed before in thin‐film electrodes by TEM and here we observed Cu 4 O 3 phase in composite electrodes. At the end of delithiation, most of the composite electrodes show reversible Cu 2 O phase rather than Cu 4 O 3 ,, which explains the high capacity reported in the present work.…”
Section: Introductionsupporting
confidence: 85%
“…In terms of the electrochemical reaction characteristics, as the lithium-ion storage electrodes deposited CuO thin film to enlarge the storage properties, the Cu 4 O 3 phase appears. It is found that Cu 4 O 3 plays an important role in the reversible electrochemical reactions that take place during the charging process (Chen et al, 2015). Recently, Wang et al have successfully synthesized Cu 4 O 3 particles for the first time using a facile wet chemical method and investigated the formation mechanism based on a series of control experiments (Wang et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The Li 2 O signal, observed in both Li-plated and exposed Cu areas, is an indication for reduction of the Cu oxides prior to or during Li plating ( Figures 9 b and 9 d). 33 , 41 The masking of the Cu 2p and O 1s signals of Cu oxides and the negative shift of the Cu 2p peaks were assigned to the lithiation of the Cu oxides ( Figures S15 and S20 ), which could be a possible reason for the thickening of the SEI at 1.4 V. 31 In addition, LiF could be a product of the Cu oxide reduction at 2–1.4 V ( reactions 4 and 5 ). 22 …”
Section: Discussionmentioning
confidence: 99%